Strategi Peningkatan Literasi Digital Di Lembaga Madrasah Ibtidaiyah - Sukma Alifatul Faizah; Risa Susanti; Machmudah Machmudah; Lusia Mumtahana (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
This study aims to describe the school's strategy in increasing the development of digital literacy in Madrasah Ibtidaiyah institutions. This research was conducted at Madrasah Ibtidaiyah Nurul Qamar 2 Putatrejo. The method used is descriptive qualitative. Data collection techniques using observation and interviews. As for the analysis using the technique of written data. The results of the interview show that the teacher uses the cultural movement method, diligently reading and visiting the library to read the existing books. In addition, to increasing digital literacy, a reward or award will be given to students who always read in the form of money or certificates. Several strategies are also used by school principals, among others, by completing facilities and targets that can support digital literacy, strengthening literacy through e-Learning, school strategies by sending teachers and education personnel to receive seminars, training, or technical assistance, and providing various books in the library.